FORMING AND DEVELOPMENT OF PEDAGOGY OF BEAUTY AS A THEORETICAL BASE OF AESTHETICAL EDUCATION OF YOUTH - V.H. Butenko (Academy of Cognitive and Natural Sciences, 2007)
It is viewed in the article the pedagogy of Beauty as a field of scientifically-pedagogical knowledge, connected with aesthetical education of youth, forming aesthetical culture of a personality, enriching of his/her spiritually-creative ties with art.